Recent developments in wearable & non-wearable point-of-care biosensors for cortisol detection. (4th March 2023) - Kaur, Simran; Gupta, Niharika; Malhotra, Bansi D.
ABSTRACT: Introduction: Cortisol is one of the most prominent biomarkers used for the detection of psychological stress and related disorders. It plays an important role in many physiological processes including immunomodulation and fat metabolism. Thus, monitoring of cortisol levels can be used to indicate different pathological conditions including stress disorders. There has been a gradual rise in the development of point of care (PoC) biosensors for continuous cortisol monitoring. Areas Covered: This review discusses recent breakthroughs toward the development of PoC sensors (wearable and non wearable) for cortisol monitoring. Challenges associated with them have also been summarized. Expert Opinion: Electrochemical PoC devices have recently emerged as a powerful tools for continuous monitoring of cortisol that can be utilized for stress management and treatment of related disorders. However, there are many challenges that should be addressed before such devices can be deployed at mass level, such as inter-individual variability, changing the device calibration with the circadian rhythm, interference from other endocrine moieties, etc. uf0001